Martin Luther King, Jr., on leadership : inspiration & wisdom for challenging times - Phillips, Donald T. (Donald Thomas), 1952- (New York : Warner Books, 2000)
"What does it mean to be a leader? How does an individual create an unstoppable organization, reshape a struggle, a competition, or even a society? Why do we listen to one man's voice, and ignore another's? In the history of leadership in America, no one has galvanized a time, place, and people more forcefully than Martin Luther King, Jr." "Now Donald T. Phillips has written an illuminating examination of the leadership style of Martin Luther King, Jr. A man who articulated a vision, crafted a strategy, and took defeats and turned them into victory, Dr. King and his life's work offer us powerful lessons that you can apply to your life, business, and any endeavor you undertake."--Jacket
pt. I. Preparing to Lead. -- 1. First Listen: Lead by Being Led. -- 2. Persuade Through Love and Nonviolence. -- 3. Learn, Learn, Learn. -- 4.
"First trade printing."
Includes bibliographical references (pages 342-345) and index
Keywords: King, Martin Luther, -- Jr., -- 1929-1968; Leadership; African Americans -- Biography; Civil rights workers -- United States -- Biography; Baptists -- United States -- Clergy -- Biography; African Americans -- Civil rights -- History -- 20th century